EŞARl VE METODOLOJiSi - Yar, Erkan (Fırat University, 2005)
AI-Ash'ari (d.324) was one of the prominent Muslim theologians and was followed as a leading figure in theological thought. At the outset he supported Mutazilite judgments in theological debates, but later on he went in for Hanbalite ones. The theological conditions of the period played crucial part in shifting from Mutazilah to the Hanbalile sect rather than the dreams or the accounts of three brothers as recorded in some works. He defended and fortified Sunnite beliefs and used rational methods to safeguard them against his opponents. The following piece of writing scrutinizes this method.
Keywords: Religious Studies; Din Araştırmaları